Crafting safer spaces for teaching about race and intersectionality in Australian Indigenous Studies - Anderson, Leticia; Riley, Lynette (The Australian Journal of Indigenous Education, 2020)
Abstract The shift to massified higher education has resulted in surges in the recruitment of staff and students from more diverse backgrounds, without ensuring the necessary concomitant changes in institutional and pedagogical cultures. Providing a genuinely inclusive and ‘safer’ higher education experience in this context requires a paradigm shift in our approaches to learning and teaching in higher education. Creating safer spaces in classrooms is a necessary building block in the transformation and decolonisation of higher education cultures and the development of cultural competency for all staff and graduates. This paper outlines an approach to crafting safer spaces within the classroom, focusing on a case study of strategies for teaching and learning about race, racism and intersectionality employed by the authors in an undergraduate Indigenous Studies unit at an urban Australian university.